KOMUNIKASI TERAPEUTIK DOKTER DAN PASIEN DALAM PENGOBATAN HOMEOPATI DI PUSAT PENGOBATAN AL JAWAD PEKANBARU - Utamy, Dyana; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Homeopathy is one of the alternative medicine option in Pekanbaru city. In the process of homeopathy treatment, doctors use the consultation as a reference in determining the appropriated medicine for the patient. Consultation process conducted by doctors and patients in the homeopathy treatment applying interpersonal communication that is therapeutic. The purpose of this research was to determine how therapeutic communication on prainteraksi phase, on the orientation/introduction phase, on the working phase and the termination phase.This research used qualitative research methods to the presentation of descriptive analysis. Informan in this research are homeopathic doctor, doctor assistant, and 5 homeopathy patient in Pusat Pengobatan Al Jawad Pekanbaru selected using purposive sampling technique. Data collection techniques used were observation, interviews, and documentation. In reaching the validity of the data in this study, researchers used an extension of participation and triangulation.The result of research showed that therapeutic communication doctor and patients in the homeopathy treatment in Pusat pengobatan Al Jawad Pekanbaru on prainteraksi phase/preparation of doctor collected information on patient and doctor designing interpersonal communication strategies to patients (openness, empathy, supportiveness, positiveness, and equality). On the phase orientation/introduction that the doctor introduced himself to the patient , showing a friendly attitude , and show the genuineness attitudes, empathy, and warmth. Therapeutic communication doctor and patients in the homeopathic treatment on the working phase of physician digging depth information about patients by implementing several methods or techniques in therapeutic communication (listening, silence, giving the open questions, giving information, advice, focus , repeat and clarification), and observing nonverbal attitude shown patients when consultation. Therapeutic communication doctor and patients in the homeopathic treatment of the termination phase is doctor conclude the consultation, giving the appropriate medicine for the patient and provide advice (advice and prohibition) when the patient is at home .Keyword : therapeutic communication, doctor and patient, homeopathy.